Enhancing Dissolution of Febuxostat: Novel Febuxostat–Syringic Acid Multicomponent Crystals via Liquid-Assisted Grinding - Gita Sri Fitri; Lili Fitriani; Erizal Zaini; Adhitya Jessica (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2026)
Gout is a chronic inflammatory disease characterized by the deposition of monosodium urate crystals in the joints, and its global prevalence continues to increase. Febuxostat, a selective xanthine oxidase inhibitor, serves as an alternative therapy for patients who cannot tolerate allopurinol. Although effective, its clinical performance is limited by very low aqueous solubility and slow dissolution due to its Biopharmaceutics Classification System (BCS) Class II characteristics. Enhancing its solubility is therefore essential to improve oral absorption. This study aimed to prepare and characterize a febuxostat–syringic acid multicomponent crystal using the liquid-assisted grinding (LAG) method and to evaluate its impact on dissolution behavior. Multicomponent crystals were prepared using various molar ratios and optimized based on differential scanning calorimetry (DSC) results. Further characterization was conducted using powder X-ray diffraction (PXRD), Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). Dissolution studies were conducted with three replicates (n=3) in phosphate–citrate buffer pH 5.5 containing 1% sodium lauryl sulfate followed by HPLC analysis. The formation of a multicomponent crystal was evidenced by a reduced melting point and decreased peak intensity, along with distinct diffraction patterns indicating lower crystallinity compared to the febuxostat and syringic acid components. FTIR analysis revealed shifts in the absorption of wave numbers, while SEM showed smaller and rougher particles, indicating improved wettability. Statistical analysis using one-way ANOVA showed that the febuxostat–syringic acid multicomponent crystal demonstrated significantly enhanced dissolution (99.21% at 60 minutes) compared with pure febuxostat (76.00% at 60 minutes) (p < 0.05). The febuxostat–syringic acid multicomponent crystal prepared via the LAG method improved the physicochemical characteristics and dissolution performance of febuxostat. This approach provides a potential strategy to enhance the bioavailability of poorly soluble BCS Class II drugs.